#### Answer

The sequence is arthematic
Recusive formula - A(n) = A(n - 1) - 4 ; A(1) = -3
Explicit formula = A(n) = -3 + (n - 1)(-4)

#### Work Step by Step

The sequence is arithmetic because there is a common difference between all the terms which is -4
Explicit formula- For this formula we need to find the d value and A(1) and we can find the d value by subtracting the second term from the first.
D = -7 - ( -3 )
D = -7 + 3
D = -4
A(1) = -3 ; We can now form the equation A(n) = -3 + A(n - 1)(-4)
Recursive- For this formula, we need the common difference and A(1) and since the common difference is the same as the d value in the explicit formula, we can use that.
Common difference = -4
A(1) = 0.3; We can now form the equation A(n) = A(n - 1) -4 ; A(1) = -3